Cooperation Efforts Between Parents and Children to Improve Children's Creativity Through Creativity Week at At-Taujieh Kindergarten - Harisman, Gani; Fauziah, Gaitsa; Rahmawati, Eka; Kurniasih, Sinta; Lusiyanti, Ayang; Sintia, Tia; Komala Sari, Siti Nur; F, Nanda Laelatul; Wahyuni, Ismi; Hermadianti, Nisa; Aulia R, Vina; Asyari, Utep; Syihatinal A, Ahlis; Rifaldi, Ari; Sunanih, Sunanih; Ghazali, Puspa Liza; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (AbdimasMu UMTAS, 2025)
The ability of creativity is the ability of a person to give birth to something new, both in the form of ideas and real works that are relatively different from what has existed. The purpose of this study was to determine the level of creativity of early childhood through a descriptive qualitative method in At-Taujieh Kindergarten, Sukamanah Hamlet. This research is a qualitative descriptive study involving 3 teachers, 30 parents, and 30 students in classes A and B, data collected through observation, interviews and documentation that researchers have conducted. The implementation of the research was carried out in collaboration with a teacher as a collaboration partner who assisted in the implementation of observations during the research so that indirectly research activities could be controlled. The results of this study show that in increasing creativity through qualitative descriptive methods as follows: 1) Children are able to express their imagination by making products from used materials 2) Children can change existing shapes into other forms 3) Children can work not the same as the results of their peers. 4) Children display the results of collaborative work between children and parents in fashion show activities. Children and parents are happy with this creativity week activity, children can add confidence with the work made, using existing materials. So increasing the creativity of early childhood in At-taujieh Kindergarten Sukamanah Hamlet can develop optimally.